The use of biologically active additives of plant origin in sausage production - A. L. Alekseev; O. E. Krotova; O. N. Konieva; S. N. Dudchenko; A. R. Kaplunenko; A. R. Strelchenko (Современная наука и инновации)
Food additives that allow regulating functional and technological properties, providing qualitative and quantitative characteristics of finished products are essential in meat technologies. Flax seed processing products, due to the high concentration of functionally valuable components and pronounced technological properties of protein and polysaccharides, are an ideal component for replacing meat raw materials in sausage products. The purpose of the work is to develop the technology of meat products enriched with biologically active additives of plant origin based on flax seeds. The theoretical part of the research was carried out on the basis of the Department of Food Technologies of DonGAU, the development of experimental batches of products was carried out in the production conditions of LLC "Meat Processing Plant", Razvilnoye village, Peschanokopsky district, Rostov region. The purpose of the research is to study the possibility of using flax seeds as a protein additive in sausage production technology. It has been established that the introduction of flax seed additives into the formulations of meat products improves the organoleptic and physico-chemical characteristics of finished products. The prototypes were distinguished by a more delicate consistency and higher uniformity of minced meat on the cut, an increase in the mass fraction of protein and a decrease in the proportion of fat were also noted. A technology for the production of sausages with a biologically active additive based on flax seeds has been developed, the functional properties and nutritional value of which, combined with economic feasibility, allow it to be used as a protein ingredient in the production of combined sausages.